2008
DOI: 10.1002/jrs.2136
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies and Raman spectroscopy of forbidden zone boundary phonons in Ni‐doped ZnO ceramics

Abstract: We present X-ray diffraction and Raman spectroscopy studies of Ni-doped ZnO (Zn 1−x Ni x O, x = 0.0, 0.03, 0.06, and 0.10) ceramics prepared by solid-state reaction technique. The presence of the secondary phase along with the wurtzite phase is observed in Ni-doped ZnO samples. The E 2 (low) optical phonon mode is seen to be shifted to a lower wavenumber with Ni incorporation in ZnO and is explained on the basis of force-constant variation of ZnO bond with Ni incorporation. A zone boundary phonon is observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 26 publications
5
24
0
Order By: Relevance
“…A strong exciton-phonon coupling was observed in Mn-doped ZnO nanowires by Liu et al [17] . In the case of Ni-doped ZnO NPs, a shifting of the E 2 (low) mode toward the lower wavelength was observed by Yadav et al, [18] which was attributed to the change in bond length by doping. Sharma et al [19] reported the shift in the E 2 (high) Raman active modes of ZnO, when doped with Ni.…”
Section: Introductionmentioning
confidence: 84%
“…A strong exciton-phonon coupling was observed in Mn-doped ZnO nanowires by Liu et al [17] . In the case of Ni-doped ZnO NPs, a shifting of the E 2 (low) mode toward the lower wavelength was observed by Yadav et al, [18] which was attributed to the change in bond length by doping. Sharma et al [19] reported the shift in the E 2 (high) Raman active modes of ZnO, when doped with Ni.…”
Section: Introductionmentioning
confidence: 84%
“…The excitations become confined within the dimension of particles, and quantum size effects are clearly examined as a high energy shift of the optical band gap [7]. Raman scattering measurements are extensively carried out to study the substitution of dopant in the ZnO host lattice [8][9][10][11][12]. This disfigures the crystal's local translational symmetry due to individuality (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The group theory predicts 12 phonon branches (9 optical and 3 acoustic modes) at the center of the Brillouin zone. Acoustic modes are generally not observed by Raman in bulk samples because of the inverse dependence of the frequency to the particle size . According to group theory prediction, the optical modes of ZnO at the center of the Brillouin zone (BZ) can be represented by the irreducible representation: normalΓopt=A1+2B1+E1+2E2.…”
Section: Resultsmentioning
confidence: 99%